Answer:
p = 2
Step-by-step explanation:
Step 1: Write equation
-5 + -2p = -9
Step 2: Solve for <em>p</em>
<u>Simplify:</u> -5 - 2p = -9
<u>Add 5 to both sides:</u> -2p = -4
<u>Divide both sides by -2:</u> p = 2
Step 3: Check
<em>Plug in p to verify it's a solution.</em>
-5 - 2(2) = -9
-5 - 4 = -9
-9 = -9
Y + 1 = -3(x - 5)
y + 1 = -3x + 15
y = -3x + 15 - 1
y = -3x + 14 <== or f(x) = -3x + 14
Answer:
<h2>(x - 6)(x - 4)</h2><h2 />
Step-by-step explanation:
x² - 10x + 24 = (x² - 6x) + (24 - 4x) = x(x - 6) + 4(6 - x) = (x - 6)(x - 4)
Answer:
bottom left
Step-by-step explanation:
...............
<h3><u><em>I</em></u><u><em>
nitial considerations</em></u></h3>
- <em>radius = 1.8 in</em>
- <em>tall = 6.7 in</em>
- <em>Volume?</em>
<h3><u><em>Resolution</em></u></h3>
<em>Volume = base area x tall</em>
<em>base area = π x (1.8in)²</em>
<em>base area = 10.179 in²</em>
<em>Volume = 10.179 in² x 6.7 in</em>
<em>Volume = 68.198 in³</em>
<h3 /><h3><em><u>Answer</u></em></h3>
<em>the volume is 68.198 in³</em>